Coordination of Mental Health Services in Humanitarian Crises : A Systematic Policy Review - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study examines the effectiveness of coordination mechanisms within mental health service delivery during humanitarian crises through a systematic review of 127 policies from 43 countries issued between 2010 and 2023. The analysis reveals that only 37.8% of policies containing coordination mechanisms can be classified as structured, while the effective implementation rate reaches 28.3% (χ²=24.67, p<.001). A subsequent meta-analysis demonstrates a significant correlation between the existence of integrated coordination systems and improved access to mental health services (r=0.73, p<.001), as well as a reduction in the severity of psychological disorders (d=0.82, 95% CI [0.76, 0.88]). Regression findings identify four primary determinants contributing to the success of coordination: centralized and directive leadership (β=0.45, p<.001), the use of integrated and real-time information systems (β=0.38, p<.001), systematically designed resource allocation strategies (β=0.35, p<.01), and the active engagement of stakeholders across sectors (β=0.31, p<.01). This study expands upon key findings by Van Long et al. (2005) concerning service fragmentation, and Martinez (2016) regarding coordination barriers, by presenting an empirically grounded model that integrates technical elements and sociocultural dimensions into the structure of coordination. Coordination effectiveness increases by up to 43% when policies adopt an adaptive and contextual approach, marking a substantial departure from conventional coordination models traditionally dominated by bureaucratic and rigid frameworks. The conceptual novelty of this study lies in developing a dynamic coordination framework that explicitly considers system complexity and the heterogeneity of crisis contexts across different global regions.